2018
DOI: 10.1038/eye.2017.291
|View full text |Cite
|
Sign up to set email alerts
|

South African Eye Study (SAES): ethnic differences in central corneal thickness and intraocular pressure

Abstract: PurposeGlaucoma is the leading cause of irreversible blindness worldwide. South Africa has a diverse population but there is a lack of published ethnic specific normative data. The purpose of the study is to determine the distribution of intraocular pressure (IOP) and central corneal thickness (CCT) values in a multi-ethnic South African population and to determine additional systemic and ocular factors that influence IOP and CCT.Patients and methodsThis cross-sectional study included a total of 402 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
3
20
0
Order By: Relevance
“…In two other studies, one reported similar CECD to ours in Chinese [ 32 ] whereas the other found a corneal endothelium with lower cell density in Americans and a higher density in Japanese [ 33 ]. When the comparison took into consideration only studies that included subjects 20 years or older ( n = 227), central cornea in the present study (504.7 ± 31.4 μm) was also thinner and/or CECD (2862.8 cells/mm 2 ) higher than found in other populations of a comparable age range in South Africa [ 4 ], Nigeria [ 13 , 34 ], Egypt [ 35 ], India [ 36 ], Iran [ 37 ], Lithuania [ 38 ], Malaysia [ 39 ], Pakistan [ 40 ], the Philippines [ 41 ], Spain [ 42 ], and the USA [ 43 ]. In the South African cohort [ 4 ], all three races (Blacks, Whites, and Mixed) had thicker central cornea than we found.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In two other studies, one reported similar CECD to ours in Chinese [ 32 ] whereas the other found a corneal endothelium with lower cell density in Americans and a higher density in Japanese [ 33 ]. When the comparison took into consideration only studies that included subjects 20 years or older ( n = 227), central cornea in the present study (504.7 ± 31.4 μm) was also thinner and/or CECD (2862.8 cells/mm 2 ) higher than found in other populations of a comparable age range in South Africa [ 4 ], Nigeria [ 13 , 34 ], Egypt [ 35 ], India [ 36 ], Iran [ 37 ], Lithuania [ 38 ], Malaysia [ 39 ], Pakistan [ 40 ], the Philippines [ 41 ], Spain [ 42 ], and the USA [ 43 ]. In the South African cohort [ 4 ], all three races (Blacks, Whites, and Mixed) had thicker central cornea than we found.…”
Section: Discussionmentioning
confidence: 86%
“…As a corollary, there may be differences in CCT and CECD across regions. However, data on CCT and CECD in normal eyes within SSA are only available for a few countries, precisely Nigeria [ 12 , 13 ], South Africa [ 4 , 14 ], Cameroon [ 15 ], Ghana [ 10 , 16 ], Ethiopia [ 17 ], and Sudan [ 18 ]. A review of these reports suggests wide variations in these parameters within SSA sub-regions [ 19 ], further substantiating the establishment of normative values for each population or subpopulation.…”
Section: Introductionmentioning
confidence: 99%
“…A worldwide meta-analysis found that the average CCT for normal eyes derived from various racial groups, regardless of the device used, was 544 μm [ 21 ], a value that is thinner than that for the Jordanian population we studied (550 μm). Comparing CCT values of our Jordanian population with Caucasian ethnicity, the most represented ethnicity in ethnicity-comparing studies [ 22 ], Caucasian ethnicity mean CCT was similar to Jordanian’s (550 ± 30.5 μm) [ 23 ]. On the other hand, African ethnicity has a lower CCT than that for Jordanians (514.77 ± 31.86) [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comparing CCT values of our Jordanian population with Caucasian ethnicity, the most represented ethnicity in ethnicity-comparing studies [ 22 ], Caucasian ethnicity mean CCT was similar to Jordanian’s (550 ± 30.5 μm) [ 23 ]. On the other hand, African ethnicity has a lower CCT than that for Jordanians (514.77 ± 31.86) [ 23 ]. It should be noted that the technique used to measure CCT can affect the results [ 24 ], and although the results from commonly used devices mostly correlate, the direct comparison between them might not be accurate [ 22 ], so that we will only include studies that used similar techniques for direct value comparison purposes.…”
Section: Discussionmentioning
confidence: 99%
“…Current studies have indicated that age, sex, race, as well as ethnicity may affect CCT. It is reported to be thinner in elders and African-Americans than in whites [6,7]. Some studies showed that men had thicker corneas [8,9].…”
Section: Introductionmentioning
confidence: 99%